Peningkatan Kualitas Pelayanan Publik melalui Penerapan Tata Kelola Pemerintahan Desa yang Efektif di Desa Pucangro - Zuli Kasmawanto (Universitas Islam Darul Ulum Lamongan, 2023)
Village government plays an important role in running and managing government at the village level, with the aim of creating a democratic life and good social services to ensure that the community is safe, peaceful, and just. The purpose of this study is to define the improvement of the quality of public services through the implementation of effective village governance carried out by the Pucangro village government. The method used in writing research is qualitative method. This research data is in the form of primary data obtained from interviews and secondary data derived from several literatures. The data obtained is then analyzed with triangulation techniques to check the credibility of the data, various methods are used to check data from the same source. The result of this study is that the Pucangro village government implements improvements in the quality of public services by preparing the Medium-Term Development Plan (RPJM), increasing transparency and accountability, involving the community in decision making, increasing the competence of Village Apparatus Human Resources and improving public service performance.